Utilization of MOOCs to Support Blended Learning at STIKes Bhakti Husada Bengkulu - Agus Riyanto; Imma Rachayu (SMART : Jurnal Teknologi Informasi dan Komputer, 2026)
The increasing adoption of digital technology in higher education has created significant opportunities for innovative learning models, particularly in health sciences institutions. This study examines the utilization of Massive Open Online Courses (MOOCs) as a supporting component in blended learning implementation at STIKes Bhakti Husada Bengkulu. The novelty of this research lies in the development and empirical validation of the Health Sciences MOOCs Integration Framework (HS-MIF)—a contextually-adapted model that integrates MOOCs platforms (Coursera, EdX, and the institutional Moodle LMS) within a structured blended learning architecture tailored for Indonesian health sciences curricula. Unlike existing frameworks that treat MOOCs as supplementary content delivery tools, HS-MIF positions MOOCs as a dynamic scaffolding mechanism that bridges pre-class preparation, synchronous clinical skill training, and post-class competency verification. A mixed-methods research design was employed, combining a quasi-experimental approach (pre-test/post-test control group design, n=94) with qualitative case study methodology. Participants were third-semester students of the Health Information Management program divided into experimental (n=47, blended learning + MOOCs) and control (n=47, conventional learning) groups. Data were collected through academic achievement tests, the validated MOOCs Learning Engagement Scale (MLES), student motivation questionnaires, and focus group discussions. Results demonstrate that the experimental group achieved significantly higher learning outcomes (mean post-test: 84.7 vs 72.3; t=6.82; p<0.001; Cohen's d=0.89), higher learning motivation scores (mean: 81.4 vs 69.2), and 87.2% course completion rates. The HS-MIF framework showed strong predictive validity (R²=0.79) in explaining learning outcome variance. These findings provide empirical evidence for the effectiveness of MOOCs-supported blended learning in Indonesian health sciences education contexts and offer actionable implementation guidelines for similar institutions.